2010
DOI: 10.1007/s12061-009-9044-6
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Spatial Homogamy. Compositional, Spatial and Regional Cultural Determinants of Regional Patterns of Spatial Homogamy in the Netherlands

Abstract: Spatial homogamy, or sharing a similarity in geographical origin, is an under-researched dimension in homogamy studies. In the Netherlands, people tend to choose spatially homogamous partners. Moreover, there is considerable regional variation in spatial homogamy, even when residential location and population density are controlled for. This study aims to explain the regional variation in spatial homogamy by means of a spatial regression. Three sets of explanations are taken into account: compositional effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Therefore, restricting the focus exclusively on trends in Euro-marriages may be too limited to see the whole picture of inter-partnering. However, inferring the incidence of unmarried cohabitation from register data is problematic because we are not entirely sure that distinction between cohabitation and just living at the same address is correctly made in the register (Haandrikman et al, 2011). In this paper, we follow a different approach by looking at the trend in the net change in the number of bi-national households, as can be inferred from published statistics.…”
Section: Euro-marriages Definedmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, restricting the focus exclusively on trends in Euro-marriages may be too limited to see the whole picture of inter-partnering. However, inferring the incidence of unmarried cohabitation from register data is problematic because we are not entirely sure that distinction between cohabitation and just living at the same address is correctly made in the register (Haandrikman et al, 2011). In this paper, we follow a different approach by looking at the trend in the net change in the number of bi-national households, as can be inferred from published statistics.…”
Section: Euro-marriages Definedmentioning
confidence: 99%
“…The problem of the structuralist approach may be that it is based on the principle of proximity. Although Haandrikman et al (2011) have shown that spatial homogamy is still a dominant factor in partner choice, its usefulness is limited for intermarriage, as the world has become more globalised. This particularly applies to Euro-marriages, as these do not automatically result from migration.…”
Section: Explanations and Interpretationsmentioning
confidence: 99%
“…Furthermore, Luxembourgers and Germans are (together with the Brits) most probable to marry a Belgian partner when living in Belgium relative to other European foreigners according to our intermarriage index. The clear predominance of marriages with a partner from a neighbouring country within the group of European bi‐national marriages reflects the importance of geographical and cultural proximity for the formation of these marriages and not at the least of language (this spatial homogamy has also been pointed out for the Netherlands in the work of Haandrikman et al ., ()). Our findings suggest that perceived distances between groups, as thematised in the traditional intermarriage literature, may just as well form a major barrier to the formation of European intermarriages.…”
Section: Discussionmentioning
confidence: 99%
“…For example, people are more likely to mate/partner with people in relatively close proximity to themselves (residential propinquity; Katz & Hill, 1958;Haandrikman, van Wissen, & Harmsen, 2011). Correspondingly, young adults can be expected to meet prospective mates/partners in college/university (Ganguli, Hausmann, & Viarengo, 2014), which is populated by people with relatively higher IQs.…”
Section: Objective and Subjective Intelligencementioning
confidence: 99%